The Role of “Guru Penggerak” in Enhancing Character Education in the Digital Era at Elementary Schools in South Sumatra - Trianti, Agus (Yayasan Sembilan Pemuda Indonesia, 2025)
Character education in Indonesia has become a top priority, especially since the introduction of the 2013 Curriculum, which has been further reinforced by the Merdeka Curriculum. This initiative aims to shape the Pancasila Student Profile, which embodies values such as independence, cooperation, religiosity, and critical thinking. Despite these efforts, the implementation of character education faces numerous challenges, particularly in the digital era. The Guru Penggerak (Teacher Mover) Program, launched by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), plays a critical role in leading educational changes and fostering students’ character development. This study employs a qualitative research design using a case study approach, involving 20 Guru Penggerak from various elementary schools in South Sumatra. Respondents were selected through purposive sampling to ensure diversity based on geographic, socio-economic, and school performance criteria. Data were collected through semi-structured interviews and focus group discussions to explore the role of technology, challenges, and strategies in character education. Thematic analysis was used to gain insights into the dynamics of character education in this specific context. This study enriches the literature by providing a contextualized perspective on character education in Indonesia, particularly amid digital challenges, and offers a foundation for developing more effective policies to support character education across regions.